Yields Losses Caused by Basal Plate Rot (Fusarium oxysporum f.sp. cepae) in Some Shallot Varieties - Hadiwiyono Hadiwiyono; Kumala Sari; Susilo Hambeg Poromarto (Universitas Sebelas Maret, 2020)
Basal plate rot or moler caused by Fusarium oxysporum f. sp. cepae (FOCe) is the most important disease of shallot. However, the information of crop losses attributed to the pathogen is still limited, especially related to resistance of shallot. This paper discusses the correlation between disease severity and resistance of some shallot varieties to yield losses. The experiment was arranged by Completely Randomized Design (CRD) with six varieties of shallot as treatments, each of which consisted of 20 shallots, with three times of replications. The independent variables were the disease severity of twisting leaf and rotting of shallot bulb. The association of disease severity versus yield losses in different varieties was based on the correlation analysis. The results showed that both variables were positively correlated to yield losses, which were significantly affected by the level of resistance. Yield losses in resistant and moderate varieties were at the ranges of 2.13-4.38 and 15, 27.26-40.04, respectively.